ANALISIS PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP KINERJA PEKERJA PADA PROYEK PEMBANGUNAN RUMAH SAKIT PRATAMA DESA HITU KABUPATEN MALTENG - Ramona Fitra Sari Lating; Rudi Serang; Wellem Gaspersz; Delvia Rimesye Apalem; Abraham Tuanakotta (Jurusan Teknik Sipil, 2023)
Occupational Safety and Health (K3) is a science for anticipating, recognizing, evaluating and controlling hazards that arise in the workplace that can impact the health and welfare of workers. The risk of falling is the highest cause of accidents. The use of adequate safety equipment such as guardrails and helmets, as well as the implementation of security procedures such as inspection of non-permanent stairs and scaffolding can reduce the risk of accidents. occupational health on work performance (K3) in the Hitu Village Primary Hospital Development project. Analysis of the data used to calculate the analysis of the application of health and work to the project